Formulation and optimization of nano-sized ethosomes for enhanced transdermal delivery of cromolyn sodium - R Rakesh; K R Anoop (Wolters Kluwer Medknow Publications, 2012)
Aim: The current study was aimed to investigate the feasibility of transdermal delivery of cromolyn sodium using a novel lipid vesicular carrier, ethosomes. Materials And Methods: Ethosomes of cromolyn sodium was prepared, optimized, and characterized for vesicle shape, vesicle size and size distribution, zeta potential, entrapment efficiency, in vitro drug release, in vitro skin permeation, in vitro skin deposition and vesicle stability. Histological examination of porcine ear skin treated with optimized ethosomal formulation was performed to study the change of skin morphologies. Results: The optimized cromolyn sodium ethosomes showed reasonable entrapment efficiency (49.88±1.84%), optimum nanometric size range (133.8 ± 7.5 nm), and high zeta potential (-69.82 ± 1.2 mV). In vitro drug release studies of optimized ethosomal formulation through cellophane membrane showed an enhanced and sustained delivery of drug compared to conventional liposomes, hydroethanolic, (45% v/v) and phosphate buffer saline PBS pH 7.4 drug solutions. The optimized ethosomal formulation showed significantly-enhanced transdermal flux (18.49 ± 0.08 mg/cm 2 /h) across porcine ear skin as compared to liposome (1.80 ± 0.12 mg/cm 2 /h), hydroethanolic drug solution (4.45 ± 0.71 mg/cm 2 /h), and PBS pH 7.4 drug solution (1.18 ± 0.35 mg/cm 2 /h). Moreover, ethosomal formulation showed better skin drug deposition (10.28 ± 0.67%) and shortest lag time (0.11 ± 0.09 h) for cromolyn sodium. Conclusion: Our significant results suggest that ethosomes can be a promising tool for transdermal delivery of cromolyn sodium.